The Antiangiogenic Effects of a Vascular Endothelial Growth Factor Decoy Receptor Can Be Monitored in Vivo Using Contrast-Enhanced Ultrasound Imaging - Flemming Forsberg; Raymond J. Ro; Andrew Marshall; Ji-Bin Liu; See-Ying Chiou; Daniel A. Merton; Priscilla Machado; Adam P. Dicker; Levon N. Nazarian (Molecular Imaging)
The development of antiangiogenic therapies has stimulated interest in noninvasive imaging methods to monitor response. We investigated whether the effects of a vascular endothelial growth factor decoy receptor (VEGF Trap, Regeneron Pharmaceuticals, Tarrytown, NY) could be monitored in vivo using contrast-enhanced ultrasonography (CEUS). Twenty nude mice (in two groups) were implanted with a human melanoma cell line (DB-1). The active group received VEGF Trap (4 × 25 mg/kg over 2 weeks), whereas the control group received an inactive protein. An ultrasound contrast agent was injected followed by power Doppler imaging (PDI) and pulse inversion harmonic imaging (PIHI; regular and intermittent). Specimens were sectioned in the same planes as the images and stained for endothelial cells (CD31), cyclooxygenase-2 (COX-2), VEGF, and hypoxia (Glut1). Measures of tumor vascularity obtained with the different imaging modes were compared to immunohistochemical markers of angiogenesis. Mean tumor volume was smaller in the active group than in the control group (656 ± 225 vs 1,160 ± 605 mm 3 ). Overall, PDI and VEGF correlated ( r = .34; p = .037). Vascularity decreased from control to treated mice with intermittent PIHI, as did the expression of CD31 and COX-2 ( p # .02), whereas VEGF increased ( p = .05). CEUS appears to allow in vivo monitoring of the antiangiogenic effects of VEGF Trap in the DB-1 human melanoma xenograft model.